2012
DOI: 10.1007/s13197-012-0859-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of drumstick (Moringa oleifera) and amaranth (Amaranthus tricolor) leaves powder on antioxidant profile and oxidative status among postmenopausal women

Abstract: Menopause is a gradual three-stage process that concludes with the end of periods and reproductive life. The antioxidant enzyme system get affected in postmenopause due to deficiency of estrogen, which has got antioxidant properties. The objective of the present study was therefore, to analyze the effect of supplementation of drumstick and amaranth leaves powder on blood levels of antioxidant and marker of oxidative stress. Ninety postmenopausal women aged 45-60 years were selected and divided into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 11 publications
5
58
1
4
Order By: Relevance
“…leaves are rich in proteins and β-carotene [4, 50], possess anti-oxidant properties [17], contain low concentrations of anti-nutrients [57–60], may be used in treating ailments [18, 61], the seeds are used as water coagulant [62], and they grow under marginal environmental conditions providing much needed ecological services (for example, shade, wind break, etc.). Moringa oleifera is naturalized while MS is indigenous to Kenya and Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
“…leaves are rich in proteins and β-carotene [4, 50], possess anti-oxidant properties [17], contain low concentrations of anti-nutrients [57–60], may be used in treating ailments [18, 61], the seeds are used as water coagulant [62], and they grow under marginal environmental conditions providing much needed ecological services (for example, shade, wind break, etc.). Moringa oleifera is naturalized while MS is indigenous to Kenya and Ethiopia.…”
Section: Resultsmentioning
confidence: 99%
“…The results are in line with a study conducted by Singh (2014) who reported that aloo bhurji supplemented with dehydrated fenugreek leaves powder were obtained highest scores for all organoleptic parameter at 7.5 per cent level of supplementation. Kushwaha (2011) reported that 10 per cent drumstick leaf powder supplementation in potato vegetable was found to be moderately acceptable with a significant difference (p0.05) from 15 per cent level of supplementation which was liked slightly.…”
Section: Moong Dalmentioning
confidence: 99%
“…In another human study, Kushwaha et al (2012) studied 30 postmenopausal women who were supplemented daily with 7 g of M. oleifera leaf powder for a period of 3 months. A control group also consisted of 30 postmenopausal women.…”
Section: Human Studiesmentioning
confidence: 99%